Identifiera kvarglömt virke med hjälp av drönare - Ferner, Erik (2020)
Large amounts of snow during winter harvesting can cause difficulties for the forwarder to find all the harvested wood. If the amount of wood left on the area is suspected to be of significant amount, a check of the area must be made. To facilitate the inventory work, the possibility of locating lost wood with the help of drones has been investigated. The purpose of this study was to use a time study to investigate if it is time saving to make inventory by drones instead of inventory on the ground. In addition, the study investigated if the wood left behind could be identified in the photos from the drone and if it were easy to mark in a GIS application. The result of this study indicates the drone already is time saving on areas more than two hectares. In total, the drone inventory was 12 percent faster than inventory on the ground. The wood left behind that was identified in the orthophotos was marked in the digital map. If wanted, the map with marked timber can be sent to a machine team before they are required to carry an extra shot on the area. The study also indicates that when inventory was made by drone the inventor had to spend 85 percent less time in the terrain compared to walking by foot. Some conclusions from the study are that it was time saving to invent using drones when only the time in the field is compared. It was also easy to identify the wood left behind in the map program and then mark it on the map. Another possibility was to use the drone images to detect damage on the ground and study the main haul roads of the area.